(untitled) (INTERNATIONAL SEMINAR, 2024)
Horror films are a genre that is widely enjoyed by the public. The purpose of this study was to explore the impact of watching religious horror films on the social behavior of society. This research used a qualitative approach with a survey method. Data were collected through questionnaires from participants selected using convenience sampling. The results of the study showed that the majority (63.6%) watched horror films for entertainment, while others were attracted by adrenaline (27.3%), moral values (18.2%), and mystical elements (15.2%). Psychological impacts included increased vigilance and courage (24.2%), as well as fear or paranoia (33.3%). The majority (66.7%) felt connected to the moral and spiritual values in the films, while others (30.3%) viewed them solely as entertainment. Strategies to cope with fear varied, ranging from rational thinking (33.3%) to increasing spiritual activities (18.2%). This study concluded that the impact of horror films is highly variable, depending on individuals’ backgrounds and experiences. Further research is recommended to expand the scope of participants and use methods beyond just surveys. .